(untitled) (Journal of Social Sciences Review, 2025)
Poliomyelitis (Polio) is a disabling disorder caused by a virus that damages the human brain. People without signs of polio and people ill with poliovirus can silently spread the virus. This study evaluates the geospatial distribution of polio cases, team distribution strategies, and identifies high-risk areas in Pakistan. The polio data was acquired from the National Emergency Operation Center (EOC) from 2017 to 2021. The collected data was analyzed in Excel sheets and then converted into a geodatabase file for geospatial processing. ArcGIS 18.8.2 was employed for the processing and interpolation to find out the spatial patterns of polio cases and guiding trends of the disease. Moran’s I analysis was used to assess the trend between polio cases and the geographical location. All the provinces and districts were divided into three classes: high, medium, and low, based on polio-verified cases. Results show that in most rural areas of Balochistan, Khyber Pakhtunkhwa, and Sindh, there was a continuous occurrence of polio cases. In 2019, there were many cases in Khyber Pakhtunkhwa, whereas in other provinces smaller number of polio-affected children. The 2020 results give a high number of polio cases in Lakki Marwat, Khyber Pakhtunkhwa, but in 2021, there was only one case reported throughout Pakistan that was in Killa Abdullah, Balochistan. Furthermore, the clustering design of polio cases is found in the southwest region of Khyber Pakhtunkhwa and the Northwest of Balochistan. This study will facilitate the planning and management of polio vaccination campaigns that aims to reach all children across Pakistan.